The Impact of Bacteriocenoses on Sperm Vitality, Immunological and Oxidative Characteristics of Ram Ejaculates: Does the Breed Play a Role? - Eva Tvrdá; Miroslava Kačániová; Andrej Baláži; Jaromír Vašíček; Jakub Vozaf; Rastislav Jurčík; Michal Ďuračka; Jana Žiarovská; Ján Kováč; Peter Chrenek (Animals, 2021)
Bacterial contamination of semen is an often overlooked, yet important, factor contributing to decreased sperm vitality. Understanding the impact of bacterial presence on sperm structural integrity and functional activity may assist the development of effective strategies to prevent, or manage, bacteriospermia in the breeding practice. The aim of this study was to describe the bacterial profiles of ram semen (n = 35), and we also focused on the associations between bacteriospermia, sperm structure, and function, as well as oxidative and inflammatory characteristics of semen. For a better insight, the samples were divided into three groups, according to the breeds used in the study: native Wallachian (NW), improved Wallachian (IW), and Slovak dairy (SD) breeds. The results showed a significantly lower motility and membrane integrity in the NW group in comparison to the IW and SD groups, which was accompanied by a significantly higher concentration of leukocytes, increased reactive oxygen species (ROS) generation, and subsequent oxidative insults to the sperm lipids and proteins. Accordingly, the NW group presented with the highest bacterial load, in which Staphylococcus and Escherichia were the predominant representatives. The Pearson correlation analysis uncovered positive relationships amongst the bacterial load and leukocytospermia (r = 0.613), the extent of lipid peroxidation (r = 0.598), protein oxidation (r = 0.514), and DNA fragmentation (r = 0.638). Furthermore, positive correlations were found between the bacterial load and pro-inflammatory molecules, such as the C-reactive protein (r = 0.592), interleukin 1 (r = 0.709), and interleukin 6 (r = 0.474), indicating a possible involvement of the immune response in the process of bacteriospermia. Overall, our data indicate that ram semen quality may be equally affected by the bacterial load and diversity. Furthermore, we can assume that the presence of bacteria in ejaculates triggers inflammatory processes, causes ROS overproduction, and, thereby, contributes to alterations in the sperm structure, while at the same time compromising the fertilization ability of male gametes.